2007
DOI: 10.2174/156720507783018271
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of ADDL-Targeting Small Molecule Drugs for Alzheimers Disease

Abstract: Amyloid beta-derived diffusible ligands (ADDLs) comprise the neurotoxic subset of soluble Abeta(1-42) oligomers, now widely considered to be the molecular cause of memory malfunction and neurodegeneration in Alzheimer's disease (AD). We have developed a screening cascade which identifies small molecule modulators of ADDL-mediated neurotoxicity. The primary screen involves a fluorescence resonance energy transfer (FRET)-based assay which selects inhibitors of Abeta1-42 oligomer assembly. The identified hits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Aβ peptide found present in AD brain is considered primarily made locally [25]. Produced in soluble monomeric form, Aβ generates soluble oligomers that are believed to be the primary toxic species [5,71], which eventually create the aggregated Aβ found in brain amyloid plaques. Following the intravenous injection of synthetic Aβ small amounts have been detected in the brain of rodents [72] and primates [73], and, reciprocally, soluble systemic Aβ has been found in plasma after central administration [74]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ peptide found present in AD brain is considered primarily made locally [25]. Produced in soluble monomeric form, Aβ generates soluble oligomers that are believed to be the primary toxic species [5,71], which eventually create the aggregated Aβ found in brain amyloid plaques. Following the intravenous injection of synthetic Aβ small amounts have been detected in the brain of rodents [72] and primates [73], and, reciprocally, soluble systemic Aβ has been found in plasma after central administration [74]).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ peptide is derived from the larger Aβ precursor protein (APP) by the action of β- and γ-secretases for the biogenesis of Aβ [3,4], which is detected normally in different cell types and tissues across evolutionary species. Aβ aggregation, in particular soluble oligomers, triggers a cascade of events that leads to neuronal dysfunction, neurodegeneration and ultimately to clinical dementia [5]. These Aβ aggregates may induce direct neurotoxic actions [6] but, additionally, may induce neurodegeneration indirectly by initiating a pro-inflammatory cascade that results in the release of inflammatory cytokines [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…These include β-amyloid contained in neuritic plaques, diffuse plaques, protofibrils, soluble oligomers and less structured aggregates. 2933 While there is no precise and generally accepted definition of the various physical forms of amyloid, all may contribute to florbetapir F 18 binding. Lockhart et al reported correlations between histochemically- and autoradiographically-demonstrated morphological forms of amyloid deposition (including diffuse plaques, neuritic plaques, cored plaques and amyloid angiopathy).…”
Section: Discussionmentioning
confidence: 99%
“…4 and 6A). The oligomeric Aβ is even 10-fold more neurotoxic than fibrils (Dahlgren et al, 2002;Look et al, 2007). However, the toxicity of Aβ to SK-N-SH cells was attenuated by co-incubation with E3 scFv.…”
Section: Discussionmentioning
confidence: 99%